Scleritis in rheumatoid arthritis: Before and during biologic era - Vergouwen, Daphne P. C.; de Jong, Pascal H. P.; Schreurs, Marco W. J.; Berge, Josianne C. Ten; Rothova, Aniki (Frontiers in Ophthalmology, 2023)
Objectives Scleritis represents a severe extra-articular manifestation of rheumatoid arthritis (RA). Recent clinical observations suggest a decreasing incidence of scleritis in RA, attributed to improved treatment options. Our study reports on the incidence and clinical characteristics of scleritis in RA observed in the biological era, and reflects on our results in a historical perspective. Methods We performed a retrospective evaluation of all 1623 consecutive patients with RA diagnosed at the department of rheumatology between 2011 and 2021 at the Erasmus Medical Center to investigate the incidence of scleritis. We also reviewed clinical and laboratory data of all patients with scleritis and RA from the department of ophthalmology at our center. In addition, we reviewed the literature on this topic and discuss our results in view of changes over time. Results The incidence of scleritis within recent series of patients with a diagnosis of RA in our tertiary center was 0,25% in 10 years (4 out of 1623; 2011-2021).The cumulative incidence of scleritis in RA based on literature review from the pre-biologic era varied from 0.7% per 8 years to 0,8% per 30 years. Manifestations and complications of scleritis remained unchanged over time, with scleral necrosis developing in more than 80% of cases and mortality of RA patients with scleritis remained similar to pre-biologic era (30% in 9 years after the onset of scleritis). The RA patients with scleritis often exhibited autoantibodies (rheumatoid factor and/or anti-citrullinated protein antibody) and erosive disease. Conclusion Although our recent series is characterized by a slightly lower incidence of scleritis in RA compared to the pre-biologic era, clinical presentation remained severe and similar to the pre-biologic era. Ophthalmologists and rheumatologists should be aware of scleritis as a severe extra-articular manifestation of RA.